2018
DOI: 10.1002/jctb.5549
|View full text |Cite
|
Sign up to set email alerts
|

Volatile fatty acids production from cheese whey: influence of pH, solid retention time and organic loading rate

Abstract: BACKGROUND The influence of pH, sludge retention time (SRT) and organic loading rate (OLR) were evaluated in the fermentation of cheese whey to produce volatile fatty acids (VFA) in a sequencing batch reactor (SBR). The reactor performance was studied at SRT of 4, 6 and 10 days and the influence of pH (5, 5.5 and 6) was determined at each SRT. The OLR effect was also studied in the range 3 to 12 g COD L‐1 d‐1, while keeping the other parameters mentioned above constant. RESULTS A more acidic pH , improved the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 22 publications
(58 reference statements)
3
9
0
Order By: Relevance
“…All experimental runs were performed in duplicate, using fresh raw cheese whey as a substrate collected from a community dairy located in Coacoatzintla Veracruz, México. The process operation was carried out under mesophilic conditions, considering two temperatures, 35 and 40 • C, and two pH values, 5.5 and 7.5. pH, and temperature values coincide with the reported conditions, where the operation is stable and VFA production is favored [7,26,27].…”
Section: Methodssupporting
confidence: 85%
See 4 more Smart Citations
“…All experimental runs were performed in duplicate, using fresh raw cheese whey as a substrate collected from a community dairy located in Coacoatzintla Veracruz, México. The process operation was carried out under mesophilic conditions, considering two temperatures, 35 and 40 • C, and two pH values, 5.5 and 7.5. pH, and temperature values coincide with the reported conditions, where the operation is stable and VFA production is favored [7,26,27].…”
Section: Methodssupporting
confidence: 85%
“…Table 1 shows the physicochemical characteristics of the fresh raw cheese whey and inoculum used in the experimental tests. It is observed that COD is significantly higher than reported by Gelegenis et al [44] and Calero et al, [7]. The inoculum showed a COD = 32.5 g COD L −1 , where 28.56 g L −1 corresponds to VFA, while the protein concentration was 7.22 g L −1 and carbohydrate concentration was 0.94 g L −1 .…”
Section: Sensibility Analysismentioning
confidence: 52%
See 3 more Smart Citations